2017
DOI: 10.1039/c7dt02632c
|View full text |Cite
|
Sign up to set email alerts
|

Two-photon spectroscopy of tungsten(0) arylisocyanides using nanosecond-pulsed excitation

Abstract: The two-photon absorption (TPA) cross sections (δ) for tungsten(0) arylisocyanides (W(CNAr)6) were determined in the 800–1000 nm region using two-photon luminescence (TPL) spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Related studies by our group have established that the sterically encumbered tungsten(0) hexakis­(2,6-diisopropylphenylisocyanide) complex W­(CNDipp) 6 is also a robust, relatively long-lived (τ­( 3 MLCT) = 75 ns in THF) excited-state reductant ( E (W + /*W 0 ) = −3.0 V vs Fc [+/0] ) capable of triggering one-electron reduction of challenging substrates, including anthracene, cobaltocenium, benzophenone, and acetophenone, upon visible light excitation. Notably, electronic modification of CNDipp by coupling of aryl substituents para to the isocyanide functionality (Figure ) leads to W­(CNDippAr) 6 oligoarylisocyanide complexes with greatly enhanced excited-state properties. Compared to W­(CNDipp) 6 , W­(CNDippPh) 6 , W­(CNDippPh OMe2 ) 6 , W­(CNDippPh OMe3 ) 6 , and W­(CNDippPh Ph ) 6 feature more intense and red-shifted MLCT absorption and emission profiles, τ­( 3 MLCT) in the microsecond range, and ϕ PL up to 0.4, while retaining comparable excited-state reduction potentials. , More recently, we also found that W­(CNDippAr) 6 complexes exhibit exceptionally high two-photon absorption cross sections (δ) in the range 1000–2000 GM (GM = Goeppert–Mayer; 1 GM = 10 –50 cm 4 s photon –1 molecule –1 ) at 812 nm, making them attractive platforms for two-photon imaging and near-IR two-photon redox catalysis …”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Related studies by our group have established that the sterically encumbered tungsten(0) hexakis­(2,6-diisopropylphenylisocyanide) complex W­(CNDipp) 6 is also a robust, relatively long-lived (τ­( 3 MLCT) = 75 ns in THF) excited-state reductant ( E (W + /*W 0 ) = −3.0 V vs Fc [+/0] ) capable of triggering one-electron reduction of challenging substrates, including anthracene, cobaltocenium, benzophenone, and acetophenone, upon visible light excitation. Notably, electronic modification of CNDipp by coupling of aryl substituents para to the isocyanide functionality (Figure ) leads to W­(CNDippAr) 6 oligoarylisocyanide complexes with greatly enhanced excited-state properties. Compared to W­(CNDipp) 6 , W­(CNDippPh) 6 , W­(CNDippPh OMe2 ) 6 , W­(CNDippPh OMe3 ) 6 , and W­(CNDippPh Ph ) 6 feature more intense and red-shifted MLCT absorption and emission profiles, τ­( 3 MLCT) in the microsecond range, and ϕ PL up to 0.4, while retaining comparable excited-state reduction potentials. , More recently, we also found that W­(CNDippAr) 6 complexes exhibit exceptionally high two-photon absorption cross sections (δ) in the range 1000–2000 GM (GM = Goeppert–Mayer; 1 GM = 10 –50 cm 4 s photon –1 molecule –1 ) at 812 nm, making them attractive platforms for two-photon imaging and near-IR two-photon redox catalysis …”
Section: Introductionmentioning
confidence: 57%
“…Compared to W(CNDipp) 6 , W(CNDippPh) 6 , W(CNDippPh OMe2 ) 6 , W-(CNDippPh OMe3 ) 6 , and W(CNDippPh Ph ) 6 feature more intense and red-shifted MLCT absorption and emission profiles, τ( 3 MLCT) in the microsecond range, and ϕ PL up to 0.4, while retaining comparable excited-state reduction potentials. 21,22 More recently, we also found that W-(CNDippAr) 6 complexes exhibit exceptionally high twophoton absorption cross sections (δ) in the range 1000− 2000 GM (GM = Goeppert−Mayer; 1 GM = 10 −50 cm 4 s photon −1 molecule −1 ) at 812 nm, 23 making them attractive platforms for two-photon imaging 24 and near-IR two-photon redox catalysis. 25 Because the photophysical properties of W(CNDippAr) 6 complexes are strongly dependent on the identity of the appended aryl group, we became interested in further examining the effects of extension of the ligand π-system on the excited-state properties of W(CNAr) 6 photoreductants.…”
Section: ■ Introductionmentioning
confidence: 97%
“…We have extended this work to include TPA cross sections for all three generations of W­(CNAr) 6 complexes in toluene solution (810 nm excitation; Table ). As δ values for [Ru­(bpy) 3 ] 2+ (bpy = 2,2′-bipyridine; δ 812 = 7 GM) and fac -Ir­(ppy) 3 (δ 800 = 20 GM) are orders of magnitude smaller at similar wavelengths, our scalable tungsten complexes have the potential to displace ruthenium and iridium photosensitizers in two-photon biological imaging, photodynamic therapy, and photoredox catalysis applications ( vide infra ).…”
Section: Resultsmentioning
confidence: 99%
“…All investigated W­(CNAr) 6 complexes displayed photoluminescence upon femtosecond-pulsed 810 nm excitation; *W­(CNAr) 6 emission spectra obtained following one- or two-photon excitation were virtually identical (Figure ), confirming that the same long-lived excited triplet ( 3 MLCT) photoreductant was generated in both cases. In 2-methyl-THF solution, W­(CNDippPh OMe2/3 ) 6 and W­(CNDippPh Ph ) 6 exhibited very large two-photon absorption cross sections [δ = 1000–2000 GM (1 GM = 10 –50 cm 4 s photon –1 molecule –1 )] upon excitation at 812 nm . We have extended this work to include TPA cross sections for all three generations of W­(CNAr) 6 complexes in toluene solution (810 nm excitation; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation